Determination of 8 biogenic amines in aquatic products and their derived products by high-performance liquid chromatography-tandem mass spectrometry without derivatization. (1st November 2021) - Zhang, Xuan; Fang, Changling; Huang, Dongmei; Yang, Guangxin; Tang, Yunyu; Shi, Yongfu; Kong, Cong; Cao, Pei; Cai, Youqiong
Highlights: HPLC-MS/MS was used for 8 BAs detection in aquatic products and their derived products. 5% perchloric acid solution and n -hexane were selected for extraction and purification. The pretreatment was rapid and simple without derivatization. A wide linear range, good sensitivity and accuracy were obtained. Abstract: A method for the determination of 8 biogenic amines in aquatic products and their derived products was established by HPLC-MS/MS without derivatization. The samples were extracted by 5% perchloric acid solution. N -hexane was used to clean the extract. The analytes were separated by a column of ACQUITY UPLC HSS T3 (100 mm × 2.1 mm, 1.8 µm), and gradient eluted with a mixed solution of (0.5% formic acid) and acetonitrile. Good linearity was obtained with correlation coefficients (R 2 ) >0.99. This method achieved higher sensitivity (from 0.1 mg/kg for tyramine, 2-phenylethylamine and tryptamine to 1.0 mg/kg for spermidine, spermine, cadaverin, histamine and putrescine). The average recoveries were demonstrated in the range of 70.9%–113.1%, with relative standard deviations (RSDs) from 0.33% to 10.81%. This method was suitable for the detection of BAs in aquatic products and their products.